Sosialisasi dan Pendampingan Efisiensi Pelayanan Bongkar Muat untuk Meningkatkan Produktivitas Tenaga Kerja di PT Sarana Bandar Nasional Cabang Tanjung Priok - Prastika, Erlinda Aulya; Keke, Yulianti; Ayutia, Yolla; Thabah, Asep Ali; Sakti, Reza Fauzi Jaya (Jurnal Abdimas Transportasi & Logistik, 2024)
This community service activity aims to improve the efficiency and quality of loading and unloading services in the Car Deck area of PT Sarana Bandar Nasional, Tanjung Priok Branch. The problem identified is the delay in the loading and unloading process caused by unorganized vehicle parking, limited communication equipment, and lack of coordination among field workers. The method applied includes direct field observation, interviews with the operations team, and training sessions for workers on safety and operational standardization. The implementation resulted in improved coordination between TKBM (loading and unloading workers) and supervisors, reduction in vehicle queueing time, and increased productivity. The Car Deck operational process became more structured and efficient. This PKM program contributes to enhancing competence in logistics service optimization within the maritime sector.